Antibiotic-Induced Oral Reactions - j - Ayatollahi; F Ezoddini Ardakani; R Bahrololoomi; F Ayatollahi (مجله دانشکده دندانپزشکی اصفهان, 2006)
The antibacterial agents are generally safe, but the list of possible adverse reactions is very long. Adverse antibiotic reactions can involve every organ and system of the body and are frequently mistaken for signs of underlying disease. Similarly, the mouth and associated structures can be affected by many antibiotic or chemicals. Regarding different parts of the oral system, these reactions can be categorized to oral mucosa and tongue, dental structures, salivary glands, periodontal tissues, cleft lip and palate, taste disturbances, muscular and neurological disorders.The knowledge about antibiotic- induced oral adverse effects helps dentists and physicians to better diag-nose oral disease, administer antibacterial agents, improve patient compliance during antibiotic therapy, and may influence a more rational use of drugs.